2006
DOI: 10.1099/mic.0.28745-0
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans SNO1 and SNZ1 expressed in stationary-phase planktonic yeast cells and base of biofilm

Abstract: The Candida albicans homologues of the most studied Saccharomyces cerevisiae stationaryphase genes, SNO1 and SNZ1, were used to test the hypothesis that, within a biofilm, some cells reach stationary phase within continuously fed, as well as static, C. albicans biofilms grown on dental acrylic. The authors first studied the expression patterns of these two genes in planktonic growth conditions. Using real-time RT-PCR (RT-RTPCR), increased peak expression of both SNZ1 and SNO1 was observed at 5 and 6 days, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Nevertheless, we identified proteins as stationary phase specific in agreement with prior publications. For instance, SNZ1 was described to have its maximum expression in 5-6-day-old suspension cultures of C. albicans (Uppuluri et al, 2006). We identified the corresponding protein Snz1p only in the stationary phase.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, we identified proteins as stationary phase specific in agreement with prior publications. For instance, SNZ1 was described to have its maximum expression in 5-6-day-old suspension cultures of C. albicans (Uppuluri et al, 2006). We identified the corresponding protein Snz1p only in the stationary phase.…”
Section: Discussionmentioning
confidence: 88%
“…SNZ1 , a member of a highly conserved gene family, was first identified through studies of proteins synthesized in stationary-phase yeast cells (Braun et al, 1996). The highly conserved gene SNO1 ( SNZ1 proximal Open reading frame) is located downstream of SNZ1 , and its regulation is coordinated with the neighboring gene through the same promoter (Uppuluri et al, 2006). Snz proteins contain no distinct functional motifs but exhibit very distant relationships with proteins involved in amino acid, vitamin, and nucleic acid biosynthesis (Dong et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This complex structure can be divided in three different layers: the basal layer, the middle layer, and the superficial layer. Studies have shown that cells of Candida biofilms have distinct metabolic activity in the different layers (La Fleur et al 2006;Uppuluri et al 2006). Thus, this variety of physiological states of biofilm cells can influence the penetration of PS and promote poor cell sensitization.…”
Section: Discussionmentioning
confidence: 99%